Educação profissional: uma análise do Pronatec, no município de Cascavel – Paraná - Biavatti, Joanna Adelia (2017)
The National Program for Access to Technical Education and Employment - Pronatec, created by the Federal Government through Law No. 12,513, of October 26, 2011, aims to offer free vocational courses in order to "expand, internalize and democratize The offer of vocational and technological education courses in the country, "with the aim of expanding educational and vocational training opportunities for young people, workers and beneficiaries of income transfer programs, among others. It is observed that the implementation of this program is constituted by the materialization of actions resulting from constant governmental discourses that endorse the speech of the representatives of the economic sectors regarding the shortage of skilled labor in Brazil and of the negative implications of this lack for the Technological development of the country. In this context, the present study proposes to analyze the relationship between the Pronatec courses, in the Technical and FIC-Initial and Continuous Training modalities, from 2011 to 2015, and the answer to the (justification) argument of existing Skilled labor, to meet the requirements of the economic productive sectors, especially in the municipality of Cascavel - PR. In order to do this, the data related to the courses offered and the needs identified by the economic sectors and the applicants, expressed by the data of the MTE, CAGED, IBGE, IPARDS, RAIS, CNI, FIEP, SEED and the Worker's Agency were interlinked. This analysis subsidized the construction of a panorama of the offer of Vocational Education, in which the representation of the demand for the Pronatec courses and the offered jobs were gathered. In this analysis it was possible to verify if the offered courses meet the requirements of the productive sectors, and also, if there was a significant increase in the occupation rates of the formal work posts, through the referrals made by the Worker Agency in the municipality of Cascavel, PR.